Discovering the Impact of Bullying on Adolescents Through Bibliometric Analysis - Wahyuni, Sri; Pranata, Satriya; Kurniawan, Wawan; Setyowati, Rahayu; Heni, Heni; Wianti, Arni; Agustini, Aat; Hijriani, Hera (Scripta Medica, 2024)
In recent years, the number of bullying cases, especially among teenagers, has been increasing, with many mass media reports on bullying cases that have resulted in the death of the victim. The aim of the study was to explore the impact of bullying on adolescents by analysing of network visualisation, overlay visualisation and density visualisation on the topic through bibliometric analysis. Records were identified through a database search at https://app.dimensions.ai/. The data obtained was then selected further by the preferred reporting items for systematic reviews and meta-analyses (PRISMA) flow diagram. Papers were limited to publication years 2019-2023 and focussed on the fields of psychology, human society, health science, clinical biomedicine, clinical education and health psychology. Data were analysed using VOSviewer, then reviewed by co-occurrence and co-author.After identifying the clusters,the impacts of bullying on adolescents were suicidal behaviour, mental disorders, non-suicidal self-injury (NSSI), loneliness, psychological distress and adolescent childhood experiences (ACEs). From the overlay visualisation, it was indicated that the newest topics that were being widely researched related to the impact of bullying on adolescents were social anxiety, suicidal ideation, depressive symptoms, suicidal thought, integrated behaviour change (IBC) and peer victimisation. From density visualisation, it was indicated that topics that were rarely researched related to the topic of the impact of bullying on adolescent were suicide attempts, early victimisation, post-traumatic stress disorder (PTSD) and suicidality. The theme regarding the impact of bullying needs and developed to be researched more deeply, especially on themes with low visualisation found in density visualisation, in order to enrich the variety of research.